Effects of Abnormal Oral Reflexes on Speech Articulation in Persian Speaking Children with Spastic Cerebral Palsy - DADGAR, Hooshang; HADIAN, Mohammad Reza; LIRA, Ortega Adriana (Iranian Journal of Child Neurology, 2016)
How to Cite This Article: Dadgar H, HadianMR, Lira OA. Effects of Abnormal Oral Reflexes on Speech Articulation in Persian Speaking Children with Spastic Cerebral Palsy. Iran J Child Neurol. Summer 2016; 10(3):28-34. Abstract Objective The purpose of this study was to investigate the relationship between the presence of abnormal oral reflexes and speech sound production in children with severe cerebral palsy. Materials&Methods Seven oral reflexes such as, rooting, mouth-opening, biting, chewing, lip, tongue, and suckling were examined in 52Persian-speaking monolingual children with spastic cerebral palsy (ages 5-10 yr).Phonetic information tests were administered to investigate their ability for articulation of the speech sounds. Results A significant relationship between three (i.e. the chewing, lip, and biting reflexes) out of the seven abnormal oral reflexes and the speech articulation was noticed. The presence of the chewing reflex was associated with deficits in production of /s, z, š,č/ sounds. The lip reflex was associated with deficits in the production of /p, m, r, j, f, č/ sounds. The biting reflex was associated with deficits in the production of /z, l, y and š/ sounds. No significant relationship was found between the rooting, mouth-opening, tongue, and suckling reflexes and sound articulation. Conclusion The presence of abnormal reflexes in the children with spastic cerebral palsy would suggest a correlation between these reflexes and sound articulation in Iranian children with spastic cerebral palsy. Hence, these observations might suggest some disturbances in normal speech development. References Surveillance of Cerebral Palsy in Europe (SCPE) Collaborative Group. Surveillance of cerebral palsy in Europe: a collaboration of cerebral palsy surveys and registers. Dev Med Child Neurol 2000; 42:816–24. Karen W Krigger. Cerebral Palsy: An Overview. American Family Physician 2006; 73, 1; 91-100. O’Shea Michael T. Cerebral palsy in very preterm infants: New epidemiological insights. Mental retardation and developmental disabilities research. Reviews2002; 8: 135–145. Krageloh-Mann AIngeborg, Cans B Christine. Cerebral palsy updates. Brain & Development 2009;31 537–544. Andersen GL, Irgens LM, Haagaas I, Skranes JS, Meberg AE, Vik T. Cerebral palsy in Norway: Prevalence, subtypes and severity. Eur J Paediatr Neurol. 2008 Jan;12(1):4-13. Nordmark E, H gglund G, Lagergren J. Cerebral palsy in southern Sweden: Prevalence and clinical features, ActaPaediatrica 2001; 90: 271 – 1276. Pfeifer LI, Silva DB, Funayama CA, Santos JL. Classification of CerebralPalsy: Association between gender, age, motor type, topography and Gross Motor Function. Arq Neuropsiquiatr2009; 67(4):1057-1061. Hagberg B. Nosology and classification of cerebral palsy. Giorn Neuropsich Eta Evol Suppl 1989; 4:12–17. Otapowicz D, Sobaniec W, Kułak W, Sendrowski K. Severity of dysarthric speech in children with infantile cerebral palsy in correlation with the brain CT and MRI. Adv Med Sci 2007; Vol. 52 • Suppl. 1 Selassie GR, Viggedal G, Olsson I, Jennische M. Speech, language, and cognition in preschool children with epilepsy. Dev Med Child Neurol 2008; 50: 432–438. Bjornson KF, McLaughlin JF, Loeser JD, Nowak-Cooperman KM, Russel M, Bader KA, Desmond SA.Oral motor, communication, and nutritional status of children during intrathecal baclofen therapy: a descriptive pilot study. Arch Phys Med Rehabil2003; 84:500-6. Mysak ED. Neuro speech therapy for the cerebral palsy (3rd ed). New York: Teacher college Press;1980.p.87-8,p.110-112. Sheppard JJ, Mysak ED. Ontogeny of infantile oral reflexes and emerging chewing. Child Dev 1984; 55:831-843. Sheppard JJ. Cranio-oropharyngeal motor patterns in dysarthria associated with cerebral palsy. J speech Hear Res 1964; 7:373-380. International Phonetic Alphabet: Handbook of the International Phonetic Association: A guide to the use of the International Phonetic AlphabetCambridge, U.K. & New York, NY: Cambridge University Press.1999. Damerchi Z, Jalilehvand N, Bakhtiari B, Keyhani MR.Development of Phonetic inventory in 2-to-6 year-old Farsi speaking children. Research in Rehabilitation Sciences2010;5:1.42-47. (In Persian). Dos Santos MT, Nogueira ML. Infantile reflexes and their effects on dental caries and oral hygiene in cerebral palsy individuals. J Oral Rehabil2005; 32; 880–885. Love RJ, Hagerman EL, Taimi EG. Speech performance, dysphagia and oral reflexes in cerebral palsy. J Speech Hear Disord 1980; 45(1):59-75. Platt LJ, Andrews G,Young M, Quinn PT. Dysarthria of adult cerebral palsy: Intelligibility and articulatory impairment. J Speech Hear Res 1980; 23(1):28-40. McFarland DH, Baum SR. Incomplete compensation to articulatory perturbation. J AcoustSoc Am1995; 97:1865-1873. Irwin OC. Communication variables of cerebral palsy and mentally retarded children. Springfield,IL: C.C. Thomas 1972. Shelley I, Velleman, Marilyn m, Vihman, phonology development in infancy and early childhood: implications for theories of language learning. In: Martha C. Pennington,editors. Phonology in Context. Basingstoke: Palgrave Macmillan;2006.p.34. Ingram TT. Clinical significance of the infantile feeding reflexes. Dev Med Child Neurol 1992; 4:159–169. Hixon T, Hardy J. Restricted motility of speech articulation in cerebral palsy. J Speech Hearing Dis1964; 29:293-306. Dubner R, Sessle BJ, Storey AT. The neural basis of oral and facial function. New York: Plenum Press. 1978.p.483.